A Community of Practice around Online Labs in Iraq: Towards Effective Support for Academics and Educational Systems in the MENA Region - Salah, Razwan Mohmed (2018)
Currently, the interest for Science, Technology, Engineering, and Mathematics disciplines in higher education has been growing through a quality improvement in curriculae, examining its impact on the educational outcomes, and ascertaining its effect on the continuous quality improvement to staff and students. Hands-on experiments with innovative instructional technologies, such as online labs, built confidence and skills of academics and students by helping them to better understand, especially in engineering and science fields. A community of practice is a group of people informally bound together by shared expertise, a set of problems, or interest in a topic and fulfils goals. In general, a community of practice focuses on sharing best practices and creating a new knowledge to advance a domain of professional practice. It informs about the appropriate activities and instructional technologies that support the education systems by making the universities a better place for developing the skills of teachers and students. The study purpose is to examine how staff and students are interested in using new instructional technologies, namely online labs, to support hands-on labs for completing their tasks. In addition, it illustrates the potential benefit of a community of practice around online labs. However, in order to facilitate the formation of a new community of practice around instructional technologies in Middle East and North Africa several presentations about online labs have been made in different universities in Iraq. Research instrument consisted of a series of questions for collecting data from the respondents by using three techniques: questionnaire, online meeting, and interview.